STRATEGI HUMAS BRIMOB POLRI DALAM PEMBENTUKAN CITRA MELALUI INSTAGRAM @HUMASKORPSBRIMOB - Noviawan Rasyid Ohorella; Bintang Aditya Pratama; Dyah Anggraini; Suhartini (Sintesa, 2026)
ABSTRACT This study discusses the strategies used by the Public Relations of the Indonesian National Police Mobile Brigade Corps (Brimob) in building and shaping a positive image through the Instagram social media account @humaskorpsbrimob. This study uses the Computer Mediated Communication theory, which assumes that human communication conducted through computer devices still adheres to the basic principles of communication, namely messages, identity, and relationships. The focus of this study highlights how digital media can be utilized to build effective communication with the public. The method used is qualitative with a descriptive approach and the paradigm used is constructivism. Data were collected through in-depth interviews, observation, documentation, and literature studies. The results show that the Public Relations of the Indonesian National Police Mobile Brigade Corps (Brimob) heavily utilizes Instagram features such as feeds, reels, stories, and live to increase interaction with the public. The use of attractive visual content and clear messages certainly helps create a positive public perception of the Indonesian National Police Mobile Brigade Corps (Brimob) institution. Trust, openness of information, and consistency in delivering messages are the main factors in successfully building a positive image thorugh social media.